2019
DOI: 10.1101/626218
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Xenotransplanted human cortical neurons reveal species-specific development and functional integration into mouse visual circuits

Abstract: How neural circuits develop in the human brain has remained almost impossible to study at the neuronal level. Here we investigate human cortical neuron development, plasticity and function, using a mouse/human chimera model in which xenotransplanted human cortical pyramidal neurons integrate as single cells into the mouse cortex. Combined neuronal tracing, electrophysiology, and in vivo structural and functional imaging revealed that the human neurons develop morphologically and functionally following a prolon… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 84 publications
4
19
0
Order By: Relevance
“…Having identified a global scaling factor for the GRN, we investigated the mechanism that sets the timescale. We reasoned that the mechanism was likely to be cell-autonomous since the temporal differences are observed between mouse and human cells grown in vitro, and it has been shown that in vitro differentiated cells transplanted to a host follow their own species-specific dynamics (30)(31)(32). Since the directed differentiation towards MNs occurs in response to Shh signalling, we hypothesized that the delay in the GRN in human compared to mouse could be a consequence of a reduced sensitivity to signalling.…”
Section: Sonic Hedgehog Signalling Sensitivity Does Not Regulate Tempomentioning
confidence: 99%
“…Having identified a global scaling factor for the GRN, we investigated the mechanism that sets the timescale. We reasoned that the mechanism was likely to be cell-autonomous since the temporal differences are observed between mouse and human cells grown in vitro, and it has been shown that in vitro differentiated cells transplanted to a host follow their own species-specific dynamics (30)(31)(32). Since the directed differentiation towards MNs occurs in response to Shh signalling, we hypothesized that the delay in the GRN in human compared to mouse could be a consequence of a reduced sensitivity to signalling.…”
Section: Sonic Hedgehog Signalling Sensitivity Does Not Regulate Tempomentioning
confidence: 99%
“…Besides the vast literature on inter-species transplantations, the topic of developmental timing was barely approached. A recent example involves transplanting ESC-derived cortical cells to assess the dynamics of neuronal differentiation, using human cortical neurons (where maturation takes months to years) transplanted into mice (where maturation takes a few weeks) (Linaro et al, 2019). The authors report that transplanted human neurons go through an extended maturation period compared to their mice counterpart, retaining juvenile properties even when the host mice was already an adult.…”
Section: Discussionmentioning
confidence: 99%
“…Intrinsic properties improved over time; membrane potential hyperpolarization, increase in maximum sodium currents, increased firing rates, dendritic length, and dendritic spine density. Two-photon and calcium imaging experiments found an increase in calcium activity in human neurons during mouse visual stimulation indicating synaptic integration within the host cortex [85].…”
Section: Abnormal Synaptogenesis In Asdmentioning
confidence: 99%